Whole-genome sequencing of marine water-derived Curvularia verruculosa KHW-7: a pioneering study - Baranda, Payal; Islam, Shaikhul; Modi, Ashish; Mistry, Harsh; Al Obaid, Sami; Ansari, Mohammad Javed; Yadav, Virendra Kumar; Patel, Ashish; Joshi, Madhvi; Sahoo, Dipak Kumar; Bariya, Himanshu (Frontiers in Microbiology, 2024)
Marine microorganisms are renowned for being a rich source of new secondary metabolites that are significant to humans.Fungi strain KHW-7 was isolated from the sea water collected from the Gulf of Khambhat, India, and identified as Curvularia verruculosa KHW-7. On a nextgeneration sequencing platform, C. verruculosa KHW-7's whole genome sequencing (WGS) and gene annotation were carried out utilizing several bioinformatic methods. The 31.59 MB genome size, 52.3% GC, and 158 bp mean read length were discovered using WGS. This genome also contained 9745 protein-coding genes, including 852 secreted proteins and 2048 transmembrane proteins. The antiSMASH algorithm used to analyze genomes found 25 secondary metabolite biosynthetic gene clusters (BGCs) that are abundant in terpene, non-ribosomal peptide synthetase (NRPS), and polyketides type 1 (T1PKS). To our best knowledge, this is the first-time whole genome sequence report of C. verruculosa. WGS analysis of C. verruculosa KHW-7 indicated that this marine-derived fungus could be an efficient generator of bioactive secondary metabolites and an important industrial enzyme, both of which demand further investigation and development.